The Effect of E-Service Quality and User Interface of PLN Mobile Application on Customer Satisfaction with Customer Trust as an Intervening Variable - Muhamad Sovian Ilham; Arthur Sitaniapessy; Joko Rizkie Widokarti (Majapahit Journal of Islamic Finance and Management, 2026)
The utilization of information technology through the PLN Mobile application is crucial for improving service quality and customer satisfaction. However, a thorough evaluation of the influence of e-service quality and user interface on customer satisfaction, especially in the UP3 Ambon region, is still needed. This study aims to analyze the direct effect of e-service quality and user interface on customer satisfaction, as well as the role of customer trust as an intervening variable. The research uses a quantitative approach, with data collected via a questionnaire from 60 respondents who are users of the PLN Mobile application. Data analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS-SEM) approach. The results of the study indicate that e-service quality has a positive and significant effect on customer satisfaction as well as on customer trust. The user interface also has a positive and significant effect on both customer satisfaction and customer trust. Moreover, customer trust has been proven to have a positive and significant effect on customer satisfaction. The customer trust variable also acts as a significant mediating variable in the relationship between e-service quality and customer satisfaction, as well as between user interface and customer satisfaction. Thus, all research hypotheses (Ha1–Ha7) are accepted. These findings emphasize the importance of e-service quality and user interface in enhancing customer satisfaction and trust toward PLN’s digital services.